IMPLEMENTASI SENSOR LEVEL UNTUK ALAT UKUR VOLUME CAIRAN SERBA GUNA DI LINGKUNGAN INDUSTRI - Sumardi, Sumardi (Transmisi, 2009)
Nowadays technology development has influence in our daily life, in all aspects, especially in industry. In industry the need of good control system could support the operational and increase the production efficiency. For example industrial automation for filling and releasing the liquid to or from the tank. There is a problem we don’t know the liquid in the tank is full or empty, say someone must look inside the tank or measure the liquid volume manually. This is not so practical according to time inefficiency and inaccurate manual measurement, cause decreasing performance of the next process. In this research we develop a measurement device, a prototype of automatic liquid volume meter based on microcontroller using PING ultrasonic sensor. By design this is more accurate than manual. This device has ability to measure the different liquid tank as long as it is a cylinder tank type. The measuring step is , first, measuring the liquid level and then calculating the liquid volume based on cylinder volume formula. Finally the result (the liquid volume) can be read in the small 2-rows monitor or LCD (Liquid Crystal Display). Keywords: liquid volume meter, ultrasonic sensor PING, level sensor, microcontroller